A method for manufacturing a quartz fiber reinforced quartz ceramic matrix composite material by stitching a prepreg laminate
Patent Information
- Application Number
- CN202611360862.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]为了解决现有技术存在的技术问题,本发明通过开发“纤维布浆料预浸+逐层铺贴缝合”的致密化复合成型技术,从单元级浆料布层调控及铺层方案设计角度出发,突破传统液相浸渍成型致密化程度低、均匀性差的共性技术难题,实现石英纤维增强石英陶瓷基复合材料高效、致密化均匀的制备,提高复合材料的力学性能和耐高温性能,增强内部均匀性,降低介电常数
1.本发明在浆料配制过程中加入有机填料,一方面可以增加浆料的粘稠度,使得浆料的分散性更好,延长浆料凝胶时间,为缝合提供更长操作窗口期时间,并且高温处理后部分转换产物可进一步提升复合材料密度;
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic composite materials technology, specifically relating to a method for preparing a quartz fiber reinforced quartz ceramic matrix composite material with prepreg laminated and stitched. Background Technology
[0002] Radomes / windows and other wave-transparent components are not only important parts of the main structure of an aircraft, but also important parts of the antenna and communication system. They can protect the antenna system from the harsh aerodynamic environment caused by high-speed flight and ensure normal signal transmission. They are multi-functional components that integrate wave transmission, heat protection, load bearing and corrosion resistance.
[0003] In the aerospace field, with the needs of modern warfare and the development of aerospace technology, new medium- and long-range missiles have the characteristics of long range, high speed (maximum speed ≥20 Ma), and long flight time (over 2000s). The missile radome is located at the front of the missile, and its function is to protect the navigation antenna from damage so that the missile can effectively hit the target. It is not only an important part of the missile's aerodynamic shape, but also a protective device for the antenna. It is an indispensable and important component of the missile. Since the total amount of aerodynamic heating borne by the radome during flight is very large, in order to ensure the aerodynamic shape of the entire missile and the normal transmission of electromagnetic signals, the ablation of the radome must be as small as possible, and excellent wave transmission performance must be maintained during flight.
[0004] Therefore, there is an urgent need to develop a radome material that is resistant to high temperatures and ablation.
[0005] Quartz ceramics have become the main radome material for tactical missiles due to their good electrical properties, low thermal conductivity, and coefficient of thermal expansion. However, the high brittleness of quartz ceramics greatly limits the reliability of their practical applications. Quartz fiber reinforced quartz composites have a melting temperature approximately equal to that of quartz glass, around 1735℃. Under aerodynamic heating conditions, they exhibit good electrical, thermal, and mechanical properties, making them the preferred material for current missile radomes.
[0006] The most common preparation method for quartz fiber reinforced quartz ceramic composites is the sol-gel method, which involves repeatedly impregnating quartz fiber preforms with silica sol. This process has many advantages, such as simplicity and high processability. However, it also has disadvantages such as low impregnation efficiency and insufficient impregnation degree, which seriously affect the mass production of related products.
[0007] During the 15th Five-Year Plan period, my country's hypersonic aircraft saw an "order-of-magnitude" increase. However, the long molding cycle of fiber-reinforced composite materials, poor internal composite uniformity, and inability to achieve functionally controllable design and preparation have become important factors restricting their low-cost and multifunctional development. Summary of the Invention
[0008] To address the technical problems existing in the prior art, this invention develops a densification composite molding technology of "fiber cloth slurry pre-impregnation + layer-by-layer laying and stitching". Starting from the perspective of unit-level slurry layer control and layup scheme design, it breaks through the common technical problems of low densification degree and poor uniformity in traditional liquid phase impregnation molding. It realizes the efficient, dense and uniform preparation of quartz fiber reinforced quartz ceramic matrix composites, improves the mechanical properties and high temperature resistance of composites, enhances internal uniformity, and reduces dielectric constant.
[0009] To address the aforementioned technical problems, the present invention adopts the following technical solution: A method for preparing a prepreg-impregnated fabric laminated and stitched quartz fiber reinforced quartz ceramic matrix composite material is characterized by comprising the steps of slurry preparation, coating and layering, vacuum pressurization, heat treatment, primary lamination, and secondary lamination; the specific operations are as follows: 1. Preparation of slurry (1) Preparation of initial slurry Add silica sol to quartz powder, stir and mix evenly, then ball mill for 12-27 hours at a speed of 200-300 r / min and a ball-to-powder ratio of 3-5:1. After ball milling, a ball mill slurry is obtained. Add an acidic substance to the ball mill slurry and stir for 10-30 minutes to obtain the initial slurry. The particle size of the quartz powder is 1000-1250 mesh; The mass concentration of the silica sol is 10-50%; The mass ratio of quartz powder to silica sol is 2:1-3; The mass ratio of acidic substances to ball milling slurry is 1:3-6; The acidic substance is one of 0.1-0.5 mol / L acetic acid solution, aluminum chloride, and ammonium chloride; Preferably, the acidic substance is one of 0.2 mol / L acetic acid solution, aluminum chloride, and ammonium chloride.
[0010] (2) Preparation of coating slurry The initial slurry is stirred and heated at 75-80℃ for 1-5 hours, organic filler is added, and stirred for 10-30 minutes to obtain the coating slurry; In coating slurries, the mass percentage of organic fillers is 1-5%; The organic filler is one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), epoxy resin (EP), and polyurethane. Preferably, the organic filler is one of polytetrafluoroethylene (PTFE), epoxy resin (EP), or polyurethane.
[0011] 2. Apply the coating layer Quartz fiber cloth is impregnated in silica sol with a solid content of 10-60%, ensuring complete immersion of the fiber cloth for 30-40 minutes. The fiber cloth is then removed, and excess silica sol is drained from the surface to obtain impregnated fiber cloth. A coating slurry is then applied to the surface of the impregnated fiber cloth. After coating, the impregnated fiber cloth is laid again, and this process is repeated until 40-80 layers are reached, resulting in a preform. The volume percentage of the stacked quartz fiber cloth in the preform is 40-45%. The quartz fiber cloth is a satin-weave fabric with a thickness of 0.2-0.4 mm and an areal density of 200-400 g / m³. 2 .
[0012] 3. Vacuum pressurization The preform is transferred to a vacuum molding machine for vacuuming and pressurization. The vacuum level is controlled at -0.09 to -0.092 MPa, and the pressure is controlled at 10-25 MPa. The vacuuming time is 5-20 minutes, and the pressurization time is 5-20 minutes. Then, it is transferred to a perforated sewing mold for normal phase needle sewing. The suture thread specification is 85-195 tex, and the number of sewing strands is 3-8. After sewing, the molded preform is obtained.
[0013] 4. Heat treatment The molded preform is transferred to an oven and dried at 80-120℃ for 6-12 hours. Then it is transferred to a muffle furnace and heat-treated at 500-1000℃ for 2-5 hours in air atmosphere to obtain a heat-treated preform.
[0014] 5. One-time compounding The heat-treated preform is immersed in 8-10 times its volume of silica sol for vacuum impregnation. The volume fraction of the silica sol is 8-56%. The vacuum degree of vacuum impregnation is -0.09 to -0.092 MPa, the impregnation pressure is 5-8 MPa, and the impregnation time is 5-20 h. After 2-5 cycles of impregnation, it is dried at 60-150℃ for 6-12 h, and then subjected to high-temperature heat treatment in air atmosphere at a temperature of 700-1000℃ for 1-3 h to obtain a rough blank with a density of 1.7-1.8 g / cm³. 3 ; Among them, the weight gain rate W of the heat-treated preform after each impregnation is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the heat-treated preform in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 8-56%.
[0015] Preferably, the volume fraction of the silica sol is 25-45%, and the b-value is 25-45%.
[0016] 6. Secondary composite After the rough blank is precision machined into the shape of an antenna radome / antenna window, it is impregnated with silica sol. The volume fraction of silica sol is 8-56%, the vacuum degree is -0.09 to -0.092 MPa, the impregnation pressure is 5-8 MPa, and the impregnation time is 5-20 h. After 1-3 cycles of impregnation, it is dried at 60-150℃ for 6-12 h, and then placed in an air atmosphere for high-temperature heat treatment at 700-1000℃ for 1-3 h to obtain a quartz fiber reinforced quartz ceramic matrix composite material. Among them, the weight gain rate W after each impregnation of the blank is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the blank in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 8-56%.
[0017] Preferably, the volume fraction of the silica sol is 25-45%, and the b-value is 25-45%.
[0018] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. In this invention, organic fillers are added during the preparation of the slurry. On the one hand, this can increase the viscosity of the slurry, making the slurry more dispersible and prolonging the gel time of the slurry, thus providing a longer operation window for suturing. On the other hand, some of the conversion products after high-temperature treatment can further increase the density of the composite material. 2. By setting a specific weight gain rate, this invention achieves high efficiency and uniformity of quartz fiber reinforced composite materials under different density or density gradient conditions, laying the foundation for the realization of low-cost preparation of composite materials, broadband wave transmission, and multifunctional integrated materials; 3. This invention can significantly improve the dispersion uniformity of the matrix material in the three-dimensional fiber fabric preform by layer-by-layer impregnation and stitching. While fully ensuring the internal quality stability of the composite material, it further realizes the designability of the composite material. By controlling the slurry formula ratio, the density of a single layer of prepreg can be pre-made in a targeted manner, laying the foundation for the homogenization and gradient controllable design and preparation of composite materials over a wide density range. 4. Compared with the traditional liquid phase circulating impregnation preparation method, this method can achieve one-time high-density molding, with high molding efficiency, significantly shortened preparation cycle, and significantly reduced material cost; 5. The quartz fiber reinforced quartz ceramic matrix composite material obtained by this invention has an internal uniformity dispersion of less than 0.03 g / cm³. 3 The room temperature tensile strength is 39.2-43.7 MPa, the room temperature flexural strength is 64.1-68.5 MPa, the compressive strength is 70.5-74.3 MPa, the dielectric constant is 2.5-3.0, and the loss tangent is <0.007. The quartz fiber reinforced quartz ceramic matrix composite material prepared by this invention was placed in an air atmosphere and heated to 1100℃ at a rate of 10℃ / min. After being kept at this temperature for 240 hours, the tensile strength was measured again to be 36.7-41.9MPa and the flexural strength was 59.7-65.4MPa. Detailed Implementation
[0019] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.
[0020] Example 1 1. Preparation of slurry (1) Preparation of initial slurry Add silica sol to quartz powder, stir and mix evenly, then ball mill for 27 hours at a speed of 300 r / min and a ball-to-powder ratio of 5:1. After ball milling, a ball mill slurry is obtained. Add an acidic substance to the ball mill slurry and stir for 30 minutes to obtain the initial slurry. The quartz powder has a particle size of 1250 mesh; The silica sol has a mass concentration of 50%. The mass ratio of quartz powder to silica sol is 2:3; The mass ratio of acidic substance to ball mill slurry is 1:6; The acidic substance is ammonium chloride.
[0021] (2) Preparation of coating slurry The initial slurry was stirred and heated at 80℃ for 5 hours, then organic filler was added and stirred for 30 minutes to obtain the coating slurry. In the coating slurry, the organic filler accounts for 5% of the mass. The organic filler is polyurethane.
[0022] 2. Apply the coating layer Quartz fiber cloth was impregnated in silica sol with a solid content of 60%, ensuring complete immersion of the fiber cloth. After immersion for 40 minutes, the fiber cloth was removed, and excess silica sol was drained from the surface to obtain impregnated fiber cloth. A coating slurry was then applied to the surface of the impregnated fiber cloth. After coating, the impregnated fiber cloth was laid again, and the process was repeated layer by layer until 80 layers were obtained, resulting in a preform. The volume percentage of the stacked quartz fiber cloth in the preform was 45%. The quartz fiber cloth is a satin-weave fabric with a thickness of 0.4 mm and an areal density of 300 g / m². 2 .
[0023] 3. Vacuum pressurization The preform is transferred to a vacuum molding machine for vacuuming and pressurization. The vacuum level is controlled at -0.092 MPa, the pressure is controlled at 25 MPa, the vacuuming time is 20 min, and the pressurization time is 20 min. Then it is transferred to a perforated sewing mold for normal phase needle sewing. The suture thread specification is 195 tex, and the number of sewing strands is 8. After sewing, the molded preform is obtained.
[0024] 4. Heat treatment The molded preform was transferred to an oven and dried at 120°C for 12 hours. Then it was transferred to a muffle furnace and heat-treated at 1000°C for 5 hours in an air atmosphere to obtain the heat-treated preform.
[0025] 5. One-time compounding The heat-treated preform was immersed in 10 times its volume of silica sol for vacuum impregnation. The volume fraction of the silica sol was 45%. The vacuum degree of impregnation was -0.092 MPa, the impregnation pressure was 8 MPa, and the impregnation time was 20 h. After 5 cycles of impregnation, it was dried at 150 °C for 6 h, and then subjected to high-temperature heat treatment in air atmosphere at 1000 °C for 3 h to obtain a rough blank with a density of 1.8 g / cm³. 3 ; Among them, the weight gain rate W of the heat-treated preform after each impregnation is controlled, W=(1-a)×b×2.2 / (a×2.2), a=the proportion of the heat-treated preform in the total volume of the impregnation system, b=the volume fraction of silica sol, b=45%.
[0026] 6. Secondary composite After the rough blank is precision machined into the shape of an antenna radome / antenna window, it is impregnated with silica sol with a volume fraction of 45%, a vacuum degree of -0.092 MPa, an impregnation pressure of 8 MPa, and an impregnation time of 20 h. After three cycles of impregnation, it is dried at 150 °C for 12 h and then subjected to high-temperature heat treatment in air atmosphere at a temperature of 1000 °C for 3 h to obtain a quartz fiber reinforced quartz ceramic matrix composite material. Among them, the weight gain rate W after each impregnation of the blank is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the blank in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 45%.
[0027] Example 2 1. Preparation of slurry (1) Preparation of initial slurry Add silica sol to quartz powder, stir and mix evenly, then ball mill for 12 hours at a speed of 200 r / min and a ball-to-powder ratio of 3:1. After ball milling, a ball mill slurry is obtained. Add an acidic substance to the ball mill slurry and stir for 10 minutes to obtain the initial slurry. The quartz powder has a particle size of 1000 mesh; The mass concentration of the silica sol is 10%; The mass ratio of quartz powder to silica sol is 2:1; The mass ratio of acidic substance to ball mill slurry is 1:3; The acidic substance is a 0.2 mol / L acetic acid solution.
[0028] (2) Preparation of coating slurry The initial slurry was stirred and heated at 75°C for 1 hour, then organic filler was added and stirred for 10 minutes to obtain the coating slurry. In the coating slurry, the organic filler accounts for 1% of the mass. The organic filler is polytetrafluoroethylene (PTFE).
[0029] 2. Apply the coating layer Quartz fiber cloth is impregnated in silica sol with a solid content of 10%, ensuring complete immersion of the fiber cloth. After immersion for 30 minutes, the fiber cloth is removed, and excess silica sol is drained from the surface to obtain impregnated fiber cloth. A coating slurry is then applied to the surface of the impregnated fiber cloth. After coating, the impregnated fiber cloth is laid again, and the process is repeated layer by layer until 40 layers are obtained, resulting in a preform. The volume percentage of the stacked quartz fiber cloth in the total volume of the preform is 40%. The quartz fiber cloth is a satin-weave fabric with a thickness of 0.2 mm and an areal density of 200 g / m³. 2 .
[0030] 3. Vacuum pressurization The preform is transferred to a vacuum molding machine for vacuuming and pressurization. The vacuum level is controlled at -0.09 MPa, the pressure is controlled at 10 MPa, the vacuuming time is 5 minutes, and the pressurization time is 5 minutes. Then it is transferred to a perforated sewing mold for normal phase needle sewing. The sewing thread specification is 85 tex, and the number of sewing strands is 3. After sewing, the molded preform is obtained.
[0031] 4. Heat treatment The molded preform was transferred to an oven and dried at 80°C for 6 hours. Then it was transferred to a muffle furnace and heat-treated at 500°C for 2 hours in an air atmosphere to obtain a heat-treated preform.
[0032] 5. One-time compounding The heat-treated preform was immersed in 8 times its volume of silica sol for vacuum impregnation. The volume fraction of the silica sol was 25%. The vacuum degree of impregnation was -0.09 MPa, the impregnation pressure was 5 MPa, and the impregnation time was 5 h. After two cycles of impregnation, it was dried at 60 °C for 12 h, and then subjected to high-temperature heat treatment in air atmosphere at 700 °C for 1 h to obtain a rough blank with a density of 1.7 g / cm³. 3 ; Among them, the weight gain rate W of the heat-treated preform after each impregnation is controlled, W=(1-a)×b×2.2 / (a×2.2), a=the proportion of the heat-treated preform in the total volume of the impregnation system, b=the volume fraction of silica sol, b=25%.
[0033] 6. Secondary composite After the rough blank is precision machined into the shape of an antenna radome / antenna window, it is impregnated with silica sol with a volume fraction of 25%, a vacuum degree of -0.09 MPa, an impregnation pressure of 5 MPa, and an impregnation time of 5 h. After one cycle of impregnation, it is dried at 60 °C for 6 h, and then placed in an air atmosphere for high-temperature heat treatment at 700 °C for 1 h to obtain a quartz fiber reinforced quartz ceramic matrix composite material. Among them, the weight gain rate W after each impregnation of the blank is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the blank in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 25%.
[0034] Example 3 1. Preparation of slurry (1) Preparation of initial slurry Add silica sol to quartz powder, stir and mix evenly, then ball mill for 20 hours at a speed of 250 r / min and a ball-to-powder ratio of 4:1. After ball milling, a ball mill slurry is obtained. Add an acidic substance to the ball mill slurry and stir for 20 minutes to obtain the initial slurry. The quartz powder has a particle size of 1200 mesh; The mass concentration of the silica sol is 30%. The mass ratio of quartz powder to silica sol is 2:2; The mass ratio of acidic substance to ball mill slurry is 1:4; The acidic substance is aluminum chloride.
[0035] (2) Preparation of coating slurry The initial slurry was stirred and heated at 78°C for 3 hours, then organic filler was added and stirred for 20 minutes to obtain the coating slurry. In the coating slurry, the organic filler accounts for 3% of the mass. The organic filler is epoxy resin (EP).
[0036] 2. Apply the coating layer Quartz fiber cloth was impregnated in silica sol with a solid content of 30%, ensuring complete immersion of the fiber cloth. After immersion for 35 minutes, the fiber cloth was removed, and excess silica sol was drained from the surface to obtain impregnated fiber cloth. A coating slurry was then applied to the surface of the impregnated fiber cloth. After coating, the impregnated fiber cloth was laid again, and the process was repeated layer by layer until 60 layers were obtained, resulting in a preform. The volume percentage of the stacked quartz fiber cloth in the total volume of the preform was 43%. The quartz fiber cloth is a satin-weave fabric with a thickness of 0.3 mm and an areal density of 300 g / m³. 2 .
[0037] 3. Vacuum pressurization The preform is transferred to a vacuum molding machine for vacuuming and pressurization. The vacuum level is controlled at -0.092 MPa, the pressure is controlled at 15 MPa, the vacuuming time is 15 min, and the pressurization time is 15 min. Then it is transferred to a perforated sewing mold for normal phase needle sewing. The suture thread specification is 125 tex, and the number of sewing strands is 5. After sewing, the molded preform is obtained.
[0038] 4. Heat treatment The molded preform was transferred to an oven and dried at 1020°C for 10 hours. Then it was transferred to a muffle furnace and heat-treated at 800°C for 3 hours in air atmosphere to obtain the heat-treated preform.
[0039] 5. One-time compounding The heat-treated preform was immersed in a silica sol solution with a volume fraction of 32% (9 times its volume) for vacuum impregnation. The vacuum degree was -0.092 MPa, the impregnation pressure was 7 MPa, and the impregnation time was 15 h. After three cycles of impregnation, it was dried at 80 °C for 10 h, and then subjected to high-temperature heat treatment in air at 850 °C for 2 h to obtain a rough blank with a density of 1.75 g / cm³. 3 ; Among them, the weight gain rate W of the heat-treated preform after each impregnation is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the heat-treated preform in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 32%.
[0040] 6. Secondary composite After the rough blank is precision machined into the shape of an antenna radome / antenna window, it is impregnated with silica sol with a volume fraction of 32%, a vacuum degree of -0.092 MPa, an impregnation pressure of 7 MPa, and an impregnation time of 15 h. After two cycles of impregnation, it is dried at 80 °C for 10 h and then subjected to high-temperature heat treatment in air atmosphere at a temperature of 850 °C for 2 h to obtain a quartz fiber reinforced quartz ceramic matrix composite material. Among them, the weight gain rate W after each impregnation of the blank is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the blank in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 32%.
[0041] The performance of the quartz fiber reinforced quartz ceramic matrix composites prepared in Examples 1-3 was tested, and the test results are as follows:
[0042] The quartz fiber reinforced quartz ceramic matrix composites prepared in Examples 1-3 were placed in air, and the temperature was increased to 1100°C at a rate of 10°C / min. After being kept at this temperature for 240 hours, the tensile strength and flexural strength were tested again, as follows:
[0043] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0044] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material, characterized in that, The process includes slurry preparation, coating and layering, vacuum pressurization, heat treatment, primary lamination, and secondary lamination. The preparation steps of the slurry are as follows: add silica sol to quartz powder, stir and mix evenly, then ball mill for 12-27 hours to obtain ball mill slurry; add acidic substance to ball mill slurry and stir to obtain initial slurry; stir and heat the initial slurry at 75-80℃ for 1-5 hours, add organic filler, stir for 10-30 minutes to obtain coating slurry; The acidic substance is one of the following: 0.1-0.5 mol / L acetic acid solution, aluminum chloride, or ammonium chloride; The organic filler is one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), epoxy resin (EP), and polyurethane.
2. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, In the slurry preparation step, the initial slurry contains quartz powder with a particle size of 1000-1250 mesh. The mass concentration of the silica sol is 10-50%; The mass ratio of quartz powder to silica sol is 2:1-3; The mass ratio of acidic substances to ball milling slurry is 1:3-6.
3. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, In the preparation step of the slurry, the organic filler accounts for 1-5% of the mass of the coating slurry.
4. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, The coating and layering steps are as follows: quartz fiber cloth is impregnated in silica sol with a solid content of 10-60%. The silica sol completely submerges the fiber cloth. After impregnation for 30-40 minutes, the fiber cloth is removed, and excess silica sol is drained from the surface to obtain impregnated fiber cloth. A coating slurry is then applied to the surface of the impregnated fiber cloth. After coating, the impregnated fiber cloth is laid again, and the operation is repeated until 40-80 layers are obtained to obtain a preform. The volume percentage of the stacked quartz fiber cloth in the total volume of the preform is 40-45%. The quartz fiber cloth is a satin-weave fabric with a thickness of 0.2-0.4 mm and a surface density of 200-400 g / m³. 2 .
5. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, The vacuum pressurization step involves transferring the preform to a vacuum molding machine for simultaneous vacuuming and pressurization. The vacuum level is controlled at -0.09 to -0.092 MPa, and the pressure is controlled at 10-25 MPa. The vacuuming time is 5-20 minutes, and the pressurization time is 5-20 minutes. Then, the preform is transferred to a perforated sewing mold for normal phase needle sewing. The suture thread specification is 85-195 tex, and the number of sewing strands is 3-8. After sewing, the molded preform is obtained.
6. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, The heat treatment step is as follows: the molded preform is transferred to an oven and dried at 80-120℃ for 6-12 hours, and then transferred to a muffle furnace and heat-treated at 500-1000℃ for 2-5 hours in an air atmosphere to obtain the heat-treated preform.
7. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, The first composite step involves immersing the heat-treated preform in 8-10 times its volume of silica sol for vacuum impregnation. The volume fraction of the silica sol is 8-56%. The vacuum degree of vacuum impregnation is -0.09 to -0.092 MPa, the impregnation pressure is 5-8 MPa, and the impregnation time is 5-20 hours. After 2-5 cycles of impregnation, the preform is dried at 60-150℃ for 6-12 hours. Then, it is subjected to high-temperature heat treatment in air at a temperature of 700-1000℃ for 1-3 hours to obtain a rough blank with a density of 1.7-1.8 g / cm³. 3 ; Among them, the weight gain rate W of the heat-treated preform after each impregnation is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the heat-treated preform in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 8-56%.
8. The method for preparing a prepreg-stitched quartz fiber reinforced quartz ceramic matrix composite material according to claim 1, characterized in that, After the rough blank is precision machined into the shape of an antenna radome / antenna window, it is impregnated with silica sol. The volume fraction of silica sol is 8-56%, the vacuum degree is -0.09 to -0.092 MPa, the impregnation pressure is 5-8 MPa, and the impregnation time is 5-20 h. After 1-3 cycles of impregnation, it is dried at 60-150℃ for 6-12 h, and then placed in an air atmosphere for high-temperature heat treatment at 700-1000℃ for 1-3 h to obtain a quartz fiber reinforced quartz ceramic matrix composite material. Among them, the weight gain rate W after each impregnation of the blank is controlled, W=(1-a)×b×2.2 / (a×2.2), where a=the proportion of the blank in the total volume of the impregnation system, b=the volume fraction of silica sol, and b is 8-56%.